A Comprehensive Proteome and Acetyl-Proteome Atlas Reveals Molecular Mechanisms Adapting to the Physiological Changes From Pre-laying to Peak-Laying Stage in Liver of Hens (Gallus gallus) - Wang, Zhang; Wang, Dandan; Jiang, Keren; Guo, Yulong; Li, Zhuanjian; Jiang, Ruirui; Han, Ruili; Li, Guoxi; Tian, Yadong; Li, Hong; Kang, Xiangtao; Liu, Xiaojun (Frontiers in Veterinary Science, 2021)
Along with sexual maturity, the liver undergoes numerous metabolic processes to adapt the physiological changes associated with egg laying in hens. However, mechanisms regulating the processes were unclear. In this study, comparative hepatic proteome and acetyl-proteome between pre- and peak-laying hens were performed. The results showed that the up-regulated proteins were mainly related to lipid and protein biosynthesis, while the down-regulated proteins were mainly involved in pyruvate metabolism and were capable to inhibit gluconeogenesis and lactate synthesis in peak-laying hens comparing with that in pre-laying hens. With unchanged expression level, the significant acetylated proteins were largely functioned on activation of polyunsaturated fatty acid oxidation in peroxisome, while the significant deacetylated proteins were principally used to elevate medium and short fatty acid oxidation in mitochondria and oxidative phosphorylation. And most of the proteins which involved in gluconeogenesis, lipid transport and detoxification were influenced by both protein expression and acetylation. Taken overall, a novel mechanism that an alternate source of acetyl coenzyme A was produced by activation of FA oxidation and pyruvate metabolism to meet the increased energy demand and lipid synthesis in liver of laying hens was uncovered. This study provides new insights into molecular mechanism of adaptation to physiological changes in liver of laying hens.